EARLY INTERVENTION STRATEGIES FOR ASD WITH AND WITHOUT PARENT ACTIVE INVOLVEMENT (Education in the 21st Century, 2023)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder of variable severity characterized by repetitive and characteristic patterns of behavior and difficulties with social communication and interaction [1]. A child with ASD is characterized by a deficit in basic communication and social interaction skills and has inappropriate interaction with their parents [2]. They pose serious behavior problems to their parents, which can cause significant pressure, stress, and discomfort in the parents, undermining their confidence in their ability as parents and bringing to tension in the family [3].Considering the state of emergency declared in Armenia and worldwide due to the COVID 19 global pandemic, we were forced to revise and reorganize our work and continue to stay close to children with ASD and their parents, providing ongoing long-distance counseling and training to parents.Taking into account the unique features of each child, based on "Individual programs," we have continued to work with parents and their children on a remote platform. During this time, parents have carried out classes with the help of a specialist. The implementation of tasks has been monitored through video calls as much as possible.Online monitoring has been carried out to check children's behavior, give instructions on a child's particular behavior, and help parents show a comparatively positive attitude towards the maladaptive behavior of their child. Likewise, strategies have been developed to reduce, change, and prevent a child's maladaptive behavior.A set of online training has been organized for parents on complicated topics. As a result, it became possible to help parents conduct correct work with their children.All outcomes and achievements were recorded and analyzed. Comparative research was done on how parent training and involvement will increase the program outcomes compared with families where parents remain on the sidelines and are not involved in their child's early intervention program.